The Role of Islamic Philanthropy in Disaster Relief in Indonesia and Japan - Firdaus, Rahmat; Fahlefi, Rizal; Wadi, Moh.; Kamali, Kamali (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2025)
This study explores the role of Islamic philanthropic instruments, zakat, waqf, and sadaqah in strengthening disaster management systems in Indonesia and Japan. Employing a library research method through systematic review and comparative analysis, the research draws on scholarly literature, institutional reports, and policy documents to assess potential integration. It finds that in Indonesia, these mechanisms offer vital resources for rapid response and recovery but face challenges related to regulatory coordination and organizational capacity. In Japan, the ethical principles underlying Islamic philanthropy resonate with existing cultural values of solidarity, presenting an opportunity to enhance community resilience models. The study concludes that strategic, context-sensitive collaboration between philanthropic organizations, government agencies, and local communities is essential to leverage these tools effectively. Such partnerships can significantly contribute to building more adaptive, inclusive, and resilient disaster management frameworks in both socio-religious contexts.